2015
DOI: 10.1016/j.anai.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondhand smoke exposure on asthma morbidity and health care utilization in children: a systematic review and meta-analysis

Abstract: Children with asthma and SHS exposure are nearly twice as likely to be hospitalized with asthma exacerbation and are more likely to have lower pulmonary function test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(84 citation statements)
references
References 51 publications
2
77
1
4
Order By: Relevance
“…Further, maternal smoking in the first year of a child’s life was associated with a greater risk of all asthma symptoms at 13–14 years, highlighting the impact of early exposure on long-term respiratory outcome [3]. ETS exposure has also been associated with more severe asthma attacks; children with asthma and ETS exposure were twice as likely to be hospitalized for asthma and had more emergency unit visits (OR 1.66, 95% CI 1.02–2.69) than unexposed asthmatics [56]. A 20% increased length of hospital stay was also found in ETS-exposed asthmatic children [57].…”
Section: Resultsmentioning
confidence: 99%
“…Further, maternal smoking in the first year of a child’s life was associated with a greater risk of all asthma symptoms at 13–14 years, highlighting the impact of early exposure on long-term respiratory outcome [3]. ETS exposure has also been associated with more severe asthma attacks; children with asthma and ETS exposure were twice as likely to be hospitalized for asthma and had more emergency unit visits (OR 1.66, 95% CI 1.02–2.69) than unexposed asthmatics [56]. A 20% increased length of hospital stay was also found in ETS-exposed asthmatic children [57].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid, forced or labored breathing, as well as retraction below the ribs or use of accessory muscles for breathing indicate severe respiratory distress and possible impairment of the lower airways. Studies have shown that asthma and bronchitis are associated with secondhand smoke in children, and that secondhand smoke children have an almost twice as high chance of presenting these respiratory problems (4,(7)(8)18) . The results of this study suggest that secondhand smoking in the home is also associated with the occurrence of treated ear disease in preschool children, corroborating previous studies (25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, respiratory system diseases represented the second leading cause of deaths in Brazil, with pneumonia being the cause for 35.6% of hospitalizations in children under the age of 5 years (6) . Evidence suggests that secondhand smoke in childhood increases the chances of hospitalization due to asthma, the demand for emergency services (7) , wheezing attacks (8) , rhinitis symptoms (9) , food sensitization (10) , caries/cavities in primary dentition (11) , atrial fibrillation (12) , behavioral problems (13) , lower engagement in school activities (14) and lower weight and height gain (15) . However, there is a lack of national studies that verify the association between secondhand smoking and respiratory symptoms easily noticeable by family members in preschool children, such as coughing, rapid breathing, "wheezing" and signs of respiratory distress, such as retraction below the ribs.…”
Section: Introductionmentioning
confidence: 99%
“…CS and air pollution were found to enhance the risk for developing asthma (Ferrante et al 2014) and are thought to trigger acute exacerbations in patients with established asthma (Guarnieri and Balmes 2014;Wang et al 2015). Moreover, occupational respiratory exposures, such as toluene diisocyanate and possibly nanoparticles, are etiological factors for the development of occupational asthma (Sharma 2010;Tarlo and Lemiere 2014).…”
Section: Asthma and Occupational Asthmamentioning
confidence: 99%